Asymmetric Synthesis of Chiral Trifluoromethyl Containing Heterocyclic Amino Acids. Issue 10 (7th July 2017) - Zhao, Liang; Zhou, Shengbin; Tong, Junhua; Wang, Jiang; Liu, Hong
Abstract : An operationally convenient, asymmetric synthesis of chiral trifluoromethyl containing heterocyclic amino acids has been developed via Michael addition reaction of chiral equivalent of Ni(II)‐complex of glycine and β ‐trifluoromethylated‐ α, β ‐unsaturated ketones. The simplicity of the experimental procedures and high stereochemical outcome of the presented method render these heterocyclic amino acids readily available for systematic medicinal chemistry studies and de novo peptide design. Abstract :